Living photosynthetic micro/nano-platforms: Engineering unicellular algae for biomedical applications - Jian Wang; Haozhe Li; Qiangfei Su; Jingwei Liu; Kang Li; Zheng Wang; Lin Wang (Bioactive Materials)
The burgeoning field of algal biomedicine capitalizes on evolutionarily refined biological systems to address critical challenges in therapeutic delivery and tissue regeneration. As autotrophic biosystems, unicellular algae uniquely possess multi-functions, including oxygen generation, dynamic motility, fluorescence imaging, and programmable biosynthesis. Their photosynthetic systems not only generate therapeutic oxygen/hydrogen gradients but also facilitate chlorophyll-mediated therapeutics through inherent fluorescence and photodynamic effects. Beyond their metabolic versatility, flagellar propulsion systems, unique morphologies (e.g., helical, elongated), and easily modified surfaces enable precision engineering of algae-based biohybrid microswimmers for spatiotemporally controlled drug delivery. This review comprehensively elucidates mechanistic foundations and biomedical applications of algae-based therapeutic platforms. Spontaneous and persistent oxygen production of algae could rescue hypoxic neurons or cardiomyocytes in myocardial infarction and ischemic stroke lesions, while ameliorating the hypoxia of skin fibroblasts to accelerate wound healing. In addition, increased oxygen levels enable the improvement of hypoxic tumor microenvironments to enhance the sensitivity of chemotherapy/radiotherapy to malignancies. Moreover, many versatile algae-based microswimmers have been developed for delivering therapeutic agents to treat gastrointestinal diseases and bacterial infections. It is believed that these photosynthetic microorganisms have great potential for being developed as next-generation platforms to address growing biomedical challenges.